(untitled) (Annals of Medical Research, 2021)
Aim: Hereditary angioedema is characterized with recurrent mucocutaneous angioedema, abdominal pain, edema of larynx and extremities. Dermal vascular thrombosis and systemic coagulation may occur in patients with hereditary angioedema due to inhibition of activated factor XII, thrombin and plasmin. Aim of this study was to screen patients with HAE for prothrombotic genetic risk factors before treatment.Material and Methods: Ten patients with hereditary angioedema who were followed up at our clinic were included in our study. The type and frequency of attack, use of prophylaxis and family history of hereditary angioedema were questioned and prothrombotic risk factors were studied.Results: Among the 10 included patients, five of them were male (50%) and five were female (50%). Four patients had abdominal edema (40%), four patients had edema of hands, feet and face (40%). One patient (10%) had heterozygous factor V G1691A mutation, another one had also heterozygous protrombin G20210A mutation. The heterozygous methylene tetrahydrofolate reductase (MTHFR) mutation were identified in seven patients (70%) and homozygous MTHFR mutation were found two patients (20%).Conclusion: In patients with hereditary angioedema, evaluation of protrombotic risk factors was crucial to estimate attack frequency-severity and treatment related thrombosis risk.Keywords: Hereditary angioedema; prothrombotic risk factors; C1 inhibitor; thrombosis.